Emerging Trends in Digital Forensics : Investigating Cybercrime - Premanand Narasimhan; Dr. N. Kala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Digital forensics is a rapidly evolving field that plays a critical role in investigating cybercrime, data breaches, and illicit activities across various domains, including blockchain, cryptocurrency, and the dark web. This paper explores key areas of digital forensics, including computer forensics, mobile forensics, network forensics, cloud forensics, IoT forensics, and embedded system forensics. Emerging trends such as drone and satellite forensics highlight the increasing scope of forensic investigations beyond traditional computing environments. Additionally, the study delves into blockchain forensics, which focuses on tracing cryptocurrency transactions to combat money laundering, ransomware payments, and illicit trading on the dark web. Advanced tools such as Chainalysis, Maltego, and SpiderFoot are employed in forensic methodologies to track digital evidence effectively. The paper also addresses challenges such as encryption, data volatility, jurisdictional barriers, and anti-forensics techniques used by cybercriminals. Legal and compliance issues, including GDPR, HIPAA, and ISO 27037, are also discussed in the context of admissibility and cross-border investigations. By analyzing real-world case studies—including the Silk Road takedown, Sony Pictures hack, and AlphaBay shutdown—this paper provides insight into the role of forensic experts in digital investigations. With advancements in artificial intelligence and machine learning, digital forensics continues to evolve, offering law enforcement and cybersecurity professionals new techniques to trace digital footprints and counter cyber threats effectively.